ANALYSIS OF RICE PRICE FORMATION AND INCREASE AT THE FARMER LEVEL - Ahmad Sayuti Royali; Fikri Nur Wafa (MESP–FEB UNS, 2024)
This study aims to determine and analyze the condition of farmers, increasing and determining rice prices at the farmer level in German Village, Sugio District, Lamongan Regency. This study used a qualitative approach with data collection methods by conducting interviews. The results of this study show that German Village is a village with high agricultural sector potential due to rainfed areas. In addition, irrigation facilities and agricultural equipment in German Village are very adequate. Furthermore, the average German Village farmer has a land area above 5,000 m2 with a harvest period of 4 months and can harvest 3 times a year. Next, in rice pricing, the role of middlemen is very large. Meanwhile, there are four ways to increase rice prices, including: selling crops through social media, price monopoly by farmers, agricultural socialization, and scheduling harvest and planting seasons.